Beyond Face Value: A Policy Analysis of Employment Equity Programs and Reporting in Ontario Public Colleges - Kipang, Shani; Zuberi, Daniyal (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Given their unique pedagogical mandate and structure, Canadian public colleges play a central role in serving groups traditionally under-represented in the post-secondary system. Yet as enrolment from these groups continues to rise, it is unclear to what extent the diversity of student bodies is reflected among faculty. In fact, while issues of faculty diversity and employment equity have gained increasing attention within Canadian universities, they have been largely overlooked within colleges. In an effort to address this gap, we have reviewed the employment equity related policies of Ontario’s five largest publicly funded colleges (otherwise known as Ontario Colleges of Applied Arts and Technology, or OCAATs). With a focus on personnel data collection and recruitment—two policy areas we will argue are particularly underdeveloped in the sector—this paper provides recommendations for future research and priorities for organizational policy development.